Evidence for Genetic Causal Association Between the Gut Microbiome, Derived Metabolites, and Age-Related Macular Degeneration: A Mediation Mendelian Randomization Analysis - Pinghui Wei; Shan Gao; Guoge Han (Biomedicines)
Background/Objectives: Despite substantial research, the causal relationships between gut microbiota (GM) and age-related macular degeneration (AMD) remain unclear. We aimed to explore these causal associations using Mendelian randomization (MR) and elucidate the potential mechanisms mediated by blood metabolites. Methods: We utilized the 211 GM dataset (n = 18,340) provided by the MiBioGen consortium. AMD outcome data were sourced from the MRC Integrated Epidemiology Unit (IEU) OpenGWAS Project. We performed bidirectional MR, two mediation analyses, and two-step MR to assess the causal links between GM and different stages of AMD (early, dry, and wet). Results: Our findings indicate that the Bacteroidales S24.7 group and genus Dorea are associated with an increased risk of early AMD, while Ruminococcaceae UCG011 and Parasutterella are linked to a higher risk of dry AMD. Conversely, Lachnospiraceae UCG004 and Anaerotruncus are protective against dry AMD. In the case of wet AMD, Intestinimonas and Sellimonas increase risk, whereas Anaerotruncus and Rikenellaceae RC9 reduce it. Additionally, various blood metabolites were implicated: valine, arabinose, creatine, lysine, alanine, and apolipoprotein A1 were associated with early AMD; glutamine and hyodeoxycholate—with a reduced risk of dry AMD; and androsterone sulfate, epiandrosterone sulfate, and lipopolysaccharide—with a reduced risk of wet AMD. Notably, the association between family Oxalobacteraceae and early AMD was mediated by valine, accounting for 19.1% of the association. Conclusions: This study establishes causal links between specific gut microbiota and AMD, mediated by blood metabolites, thereby enhancing our understanding of the gut–retina axis in AMD pathophysiology.